Pengaruh Korean Wave, Perilaku Fan Entrepreneurship Dan Media Sosial Terhadap Minat Berwirausaha Pada Komunitas Armys.Luv Kota Jambi - Putri Aulia Laillatul Isnainy; Sigit Indrawijaya; Musnaini Musnaini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to analyze and determine the influence of the Korean wave, fan entrepreneurship behavior, and social media on entrepreneurial interest in the Armys.Luv community in Jambi City partially and simultaneously. This research uses a quantitative approach with an associative method. The population in this research were BTS fans in the Armys.Luv community in Jambi City with using a sample of 95 respondents. Research data was obtained by distributing research questionnaires online. The analysis tool used is the SPSS version 25 application. The research results show that the Korean wave, fan entrepreneurship behavior and social media have a significant partial and simultaneous effect on interest in entrepreneurship in the Armys.Luv community in Jambi City. It is known that there is a market share in the Korean wave sector, so it can be utilized as a business opportunity. So besides enjoy the work and culture and being a fan, it can also learn and get to know more about things that are currently popular and trending on social media at the moment so that can use as business opportunities.